Associations Between Worksite Walkability, Greenness, and Physical Activity Around Work. Issue 2 (February 2020) - Marquet, Oriol; Floyd, Myron F.; James, Peter; Glanz, Karen; Jennings, Viniece; Jankowska, Marta M.; Kerr, Jacqueline; Hipp, J. Aaron
This article explores the role of the work environment in determining physical activity gained within and around the workplace. With most adults spending more than half of their waking day at work, the workplace is a promising venue for promoting physical activity. We used a sample of 147 employed women—median age = 53 years old; 42% meeting Centers for Disease Control and Prevention (CDC) physical activity recommendations—wearing a GPS device and accelerometer on the hip for 7 days to assess location and physical activity at minute-level epochs. We analyzed the association between geographic information systems (GIS) measures of walkability and greenness around the workplace and the amount of physical activity gained while in the work neighborhood. Our results showed that working in high walkable environments was associated with higher levels of moderate to vigorous physical activity while at work, and with higher moderate to vigorous physical activity gained within the work neighborhood. Increasing walkability levels around workplaces can contribute to increasing physical activity of employees.